Teacher’s Epistemic Beliefs about the Integration of Digital Literacy in the EFL Classroom (International Journal of Language Teaching and Education, 2019)
Digital literacy is the skill which highly important to effectively use digital technology and to survive in the digital-rich environment. The study examines two in-service teachers’ epistemic beliefs about the integration of digital literacy in the English Foreign Language classroom. The participants of the study are two English teachers in senior high school in Indonesia. The case study research design was used in the study, and qualitative content analysis was used to analyze the data obtained from the participants. The finding of the study revealed that digital literacy was perceived as a basic skill for learning with digital technology, a skill for collaboration and communication, a skill for evaluating information, and skill for reproduction. The study provided more insight to enhance the understanding of in-service teachers’ belief about the integration of digital literacy.